Efeitos do exercício físico na cognição de idosos pré-frágeis e frágeis - Rossi, Paulo Giusti (2021)
Frailty syndrome is characterized as an important geriatric syndrome because it is associated with a greater risk of functional decline, falls, institutionalization, hospitalization and death. Besides, cognition is an important factor and seems to be involved as part of the frailty syndrome, so that most of these older adults presents cognitive decline associated. The most used form of treatment is physical exercise, being multicomponent the most effective, and the treatment of older adults at risk of frailty is a key factor to prevent progressions and consequently worsening in the phenotypic aspects presented in the syndrome. Therefore, the following thesis was divided into two studies, and Study I, entitled “Effects of physical exercise on the cognition of older adults with frailty syndrome: A systematic review and meta-analysis of randomized trials”, aimed to analyze the effects of physical exercise without the addition of a specific cognitive stimuli on the cognition of community-dwelling older adults with frailty syndrome; and Study II, entitled “Effects of multicomponent physical exercise on cognition and performance in a dual-task test of pre-frail older adults: a randomized, blinded, controlled study”, aimed to analyze the effects of a multicomponent training intervention without specific cognitive stimuli on global cognition and in a challenging dual-task performance test in community-dwelling pre-frail older adults. To the development of the second study, a protocol for pre-frail older adults was developed and published. The protocol consisted of warm-up, aerobic exercises, balance, muscle strengthening and cool-down according to the American College of Sports Medicine guidelines, lasting 16 weeks, 3 times per week, 60 minutes each session. The results from Study I allow the conclusion that physical exercise, even without specific cognitive stimuli, is able to improve the cognition of older adults with frailty syndrome. However, Study II demonstrated that specifically in pre-frail older adults, physical exercise alone does not show the potential to improve performance in dual-task activity, suggesting a more specific approach to improve this aspect.